Protective Role of Hsp27 in the Nonylphenol-Induced Locomotory and Longevity Toxicity - Dwivedi, Shiwangi; Francis, Kean Anthony Daniel; Sharma, Anurag (Journal of Health and Allied Sciences NU, 2023)
Background Gut health is directly proportional to an organism's fitness. Our recent study showed a functional link between oxidative stress and heat shock protein 27 (Hsp27, a stress protein) in the Drosophila larval gut, which coordinates the nonylphenol (an endocrine disruptor) allied sub-cellular and developmental adversities.Objective In continuation with the prior study, the present study aimed to explore the association of Hsp27 with locomotory and survival against nonylphenol-induced toxicity in the Drosophila gut.Methods and Methodology The freshly emerged adult flies were exposed to nonylphenol (5.0 µg/mL) for 10 to 40 days, and their locomotory performance (climbing activity) and survivability were assessed. ANOVA was used to evaluate the statistical significance of the mean values in control and treated flies.Results Nonylphenol exposure markedly influenced locomotory activity and survivability after 30 to 40 days. For instance, ∼76% (40 days) declined locomotor behavior, and ∼35% (40 days) reduced survivability was observed. While the overexpression of Hsp27 in the organism's gut showed improvement in locomotory performance and survivability after 30 to 40 days. No significant alteration in locomotory performance and survivability was observed after 10 to 20 days of nonylphenol exposure.Conclusion The present study illustrates that Hsp27 overexpression in the Drosophila gut improves the locomotory performance and survivability in the nonylphenol exposed Drosophila. This also indicates the possible connection between the gut and organismal fitness.
Keywords: Nonylphenol; Hsp27; locomotion; survival; Drosophila